Usury in the School of Salamanca (Journal of the Sociology and Theory of Religion, 2026)
This article examines the doctrine of usury in the School of Salamanca as a pivotal moment of transition between medieval scholasticism and modern economic thought. Without abandoning the traditional prohibition of usury, Salamancan theologians and jurists reinterpreted its foundations through the development of so-called extrinsic titles, which made it possible to justify compensations linked to risk, the temporary deprivation of capital, and opportunity cost. Drawing on an analysis of authors such as Vitoria, Soto, Azpilcueta, Molina, Mercado, and Covarrubias, the article highlights a shared methodological framework alongside the absence of a strictly unified doctrine. Although the School of Salamanca did not formulate a modern concept of interest, it introduced elements—time, risk, and alternative uses of money—that proved fundamental to later theories of capital and interest.
Keywords: School of Salamanca; usury; interest; scholastic economic thought; capital and time; history of economic thought